An artificial sensory neuron with visual-haptic fusion - Changjin Wan (Nature Portfolio, 2020)
Designing bioinspired perceptual system remains a challenge. Here, the authors report a bimodal artificial sensory neuron, integrating a resistive pressure sensor, a perovskite-based photodetector, a hydrogel-based ionic cable, and a synaptic transistor, to implement the visual-haptic fusion for motion control and patterns recognition.